Real World Long-term Assessment of The Efficacy of Tocilizumab in Patients with COVID-19: Results From A Large De-identified Multicenter Electronic Health Record Dataset in the United States. (December 2021) - Nigo, Masayuki; Rasmy, Laila; May, Sarah B.; Rao, Aishwarya; Karimaghaei, Sam; Kannadath, Bijun Sai; De la Hoz, Alejandro; Arias, Cesar A.; Li, Liang; Zhi, Degui
Highlights: The real-world efficacy of tocilizumab was evaluated in COVID-19 patients. This study was conducted with a large US multicenter de-identified database. The temporal short-term benefit in survival curves was observed. The benefit was observed in patients requiring high amounts of supplemental oxygen. Long-term benefit vs risk of tocilizumab should be evaluated in follow up studies. Abstract: Background: Studies have shown conflicting results on the efficacy of tocilizumab (TCZ) for patients with COVID-19, with many confounders of clinical status and limited duration of the observation. Here, we evaluate the real-world long-term efficacy of TCZ in COVID-19 patients. Methods: We conducted a retrospective study of hospitalized adult patients with COVID-19 using a large US-based multicenter COVID-19 database (Cerner Real-World Data; updated in September, 2020). The TCZ group was defined as patients who received at least one dose of the drug. Matching weight (MW) and a propensity score weighting method were used to balance confounding factors. Results: A total of 20, 399 patients were identified. 1, 510 and 18, 899 were in the TCZ and control groups, respectively. After MW adjustment, no statistically significant differences in all-cause mortality were found for the TCZ vs. control group (Hazard Ratio [HR]:0.76, p=0.06). Survival curves suggested a better trend in short-term observation, driven from a subgroup of patients requiring oxygen masks, BIPAP or CPAP. Conclusion: We observed a temporal (early) benefit of TCZ, especially in patients on non-invasive high-flow supplemental oxygen. However, the benefit effects faded with longer observation. The long-term benefits and risks of TCZ should be carefully evaluated with follow-up studies.